2017
DOI: 10.7759/cureus.1222
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report on Complicated Tuberculous Meningitis

Abstract: Tuberculous meningitis (TBM) is associated with significant complications of central nervous system. It is accompanied by nonspecific and heterogeneous clinical symptoms. We focused on the significance of early diagnosis and prompt treatment. We describe a case of TBM in a 19-year-old Asian female. She had a progressive motor weakness with no sensory findings. She was started on antituberculous therapy. Her magnetic resonance imaging (MRI) contrast of dorsolumbar spine showed syringomyelia. Her culture and sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The traditional treatment for pulmonary TB has been standardized to the RIPE [rifampin (RIF), isoniazid (INH), pyrazinamide, ethambutol) therapy for 2 months followed by RI (rifampin, isoniazid) for 10 months [ 20 , 23 , 37 , 38 , 39 ]. The empirical treatment for TBM remains the same as the treatment for pulmonary TB; the empirical treatment is warranted when clinical features and CSF findings are suggestive of TBM, even before microbiologic confirmation, since timely treatment dramatically improves the outcome of TBM [ 20 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The traditional treatment for pulmonary TB has been standardized to the RIPE [rifampin (RIF), isoniazid (INH), pyrazinamide, ethambutol) therapy for 2 months followed by RI (rifampin, isoniazid) for 10 months [ 20 , 23 , 37 , 38 , 39 ]. The empirical treatment for TBM remains the same as the treatment for pulmonary TB; the empirical treatment is warranted when clinical features and CSF findings are suggestive of TBM, even before microbiologic confirmation, since timely treatment dramatically improves the outcome of TBM [ 20 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that patients who present with TB with past medical history conditions are not treated similarly. For example, HIV patients are given the standard regimen of 2 months RIPE followed by 10 months of RI, but also given an ART therapy after [ 20 , 23 , 37 , 38 , 39 ]. Patients who develop syndrome of inappropriate antidiuretic hormone (SIADH) from M. tuberculosis infection should engage in fluid restriction and take medications such as furosemide and demeclocycline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, multiple authors have reported high failure rate and poor long-term results of surgical treatment of arachnoiditisassociated syringomyelia [19][20][21]. Conservative treatment by steroids along with anti-tubercular therapy has been shown to produce neurological recovery in such patients [22,23]. Proponents of conservative treatment argue that the presence of arachnoiditis at different spinal levels makes the outcome of surgery hard to predict and unreliable.…”
Section: Discussionmentioning
confidence: 99%